2008
DOI: 10.1007/s10551-008-9832-y
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Advertising of Controversial Products in China: An Empirical Approach

Abstract: advertising, alcohol, China, condoms, controversial products,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
0
19
1
2
Order By: Relevance
“…6; as protection technology to support market monitoring, reaction, as well as prevention effort . Conversely, the finding does not support the claimed by Fam, Waller and Yang (2009) that many organisations used offensive advertisement to gain consumers awareness about the counterfeit products, whilst which platform such offensive awareness is being created unknown. Further to this, the finding does not support the view that mass production and information overload, which occurred in the recent time has made consumers unknowingly buy an imitation product Stravinskiene et al (2013), but how such information overload happened is not clearly stated.…”
Section: Discussion Of Findingscontrasting
confidence: 73%
See 1 more Smart Citation
“…6; as protection technology to support market monitoring, reaction, as well as prevention effort . Conversely, the finding does not support the claimed by Fam, Waller and Yang (2009) that many organisations used offensive advertisement to gain consumers awareness about the counterfeit products, whilst which platform such offensive awareness is being created unknown. Further to this, the finding does not support the view that mass production and information overload, which occurred in the recent time has made consumers unknowingly buy an imitation product Stravinskiene et al (2013), but how such information overload happened is not clearly stated.…”
Section: Discussion Of Findingscontrasting
confidence: 73%
“…The counterfeit or deceptive goods are produced and sold to mislead consumers into believing the products are genuine. Fam, Waller and Yang (2009) found that many organisations used offensive advertisement to gain consumers awareness about counterfeit products. In a similar research, Stravinskiene et al (2013) shows that mass production and information overload, which occurred in the recent time has made consumers unknowingly buy an imitation product.…”
Section: Theoretical and Empirical Perspectives Of Counterfeitmentioning
confidence: 99%
“…Not all controversial ads are unethical, and vice versa. Controversial ads can also generate positive effects such as in social marketing awareness campaigns (Fam et al 2009). Moreover, since ethics is based on moral philosophies which fluctuate with individual judgement, "there is no such thing as a right/wrong or ethical/unethical ad, there are only latitudes [or boundaries] of ethicality" (Bush and Bush 1994, p. 33).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the external validity of the research, the results were replicated for two kinds of controversial taboo appeal; one related to sexuality, and the other to death. Second, our findings provide insight into the controversial advertising literature, which has focused mainly on controversial products (Fam et al 2009) and offline controversial appeal effects on consumers (except for Kerr et al 2012). We extend this literature by investigating the role of the communication medium in advertisement evaluation, through a comparison of consumer evaluations of the same controversial taboo ad for a fictitious brand in a newspaper, as well as in a Facebook Page.…”
Section: Introductionmentioning
confidence: 65%
“…Advertisements can be regarded as controversial if (1) they feature products that are 'unmentionable' (Wilson and West 1981;Katsanis 1994), 'sensitive' (Shao and Hill 1994;Fahy et al 1995), 'offensive' (Barnes and Doston 1990;Waller 1999;Fam and Waller 2003;Prendergast and Chia Hwa 2003), 'controversial' (Rehman and Brooks 1987;Fam et al 2009); (2) or because the creative execution is controversial and provocative (Dahl et al 2003;De Pelsmacker and Van Den Bergh 1996;Manceau and Tissier-Desbordes, 2006;Pope et al 2004;Vézina and Paul 1997). Controversial taboo advertising has been used as a communication strategy to break through clutter and to grab audience attention (Dahl et al 2003;Prugsamatz et al 2006;Vézina and Paul 1997;Waller 2005).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%